1990
DOI: 10.1042/bj2650343
|View full text |Cite
|
Sign up to set email alerts
|

How does fluoroaluminate activate human platelets?

Abstract: Platelet activation induced by NaF or fluoroaluminate (AlF4-) was studied. The latter has been described to substitute for the gamma-phosphate group of the GTP molecule. With 10 mM-NaF, a concentration unable to induce any measurable Ca2+ mobilization (as measured with Indo 1), addition of AlCl3 potentiated platelet aggregation, thromboxane synthesis, diacylglycerol formation and p43 phosphorylation, without any increase in intracellular Ca2+. Neither phosphoinositide hydrolysis nor phosphatidic acid formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…These authors proposed that the fluoroaluminate complex, formed upon the association of NaF and AlCl 3 , may be responsible for the observed effects. We have shown here that Al 3+ , at concentrations higher than those used by Rendu et al (11), promoted platelet aggregation and peroxidation in the absence of NaF. Recently, Al 3+ has been shown to induce lipid peroxidation in brain tissue of mice chronically exposed to the metal (6).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These authors proposed that the fluoroaluminate complex, formed upon the association of NaF and AlCl 3 , may be responsible for the observed effects. We have shown here that Al 3+ , at concentrations higher than those used by Rendu et al (11), promoted platelet aggregation and peroxidation in the absence of NaF. Recently, Al 3+ has been shown to induce lipid peroxidation in brain tissue of mice chronically exposed to the metal (6).…”
Section: Discussionmentioning
confidence: 75%
“…Earlier, Rendu et al (11) reported that Al 3+ at concentrations similar to those present in the blood circulation potentiated NaF-elicited platelet aggregation, as well as diacylglycerol and 43-kDa phosphorylation. These authors proposed that the fluoroaluminate complex, formed upon the association of NaF and AlCl 3 , may be responsible for the observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of platelets is connected with shape changes. Rendu et al [78] observed that incubation of platelets with NaF (5-10 mM) induced only slight morphological changes. Addition of 10 M AlCl 3 resulted in aggregation.…”
Section: Plateletsmentioning
confidence: 99%
“…AIF 4 induces platelet activation by mechanisms not fully elucidated. This compound (10 mM or less) produces diacylglycerol and TxB2, without activating PLC, and increases PKC activity without an apparent increase of intracellular Ca 2+ [15]. At higher concentrations (20 mM or more), A1F 4 activates PLC and liberates TxB2 being the two events independent [7,14].…”
Section: Introductionmentioning
confidence: 99%